The infl uence of the norms of legal systems in the caste system in India. - Taubaldieva, D. S.; Alipbayeva, B. A. (Journal of Oriental Studies, 2016)
This article is dedicated to the infl uence of the norms of legal systems in the caste system in India. Subject caste system in India is relevant. Legal rules should determine the right of every citizen. At this time, the problem of caste system reduces the rights of every citizen of India. In developing countries, the discrimination of the people will always affect the opposite way. Adoption of the law, rules of legal systems does not eliminate all the old traditional legal rules, but will gradually eliminate the ability to use.